2022
DOI: 10.3389/fonc.2021.746304
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Genetic Characteristics of Thymoma Patients With Autoimmune Hepatitis and Myocarditis

Abstract: BackgroundOur study investigated a special series of thymoma with autoimmune hepatitis and myocarditis and tried to reveal the gene expression profiles of this series of thymoma.MethodsFrom 2011 to 2019, a total of 13 special thymoma patients presented with autoimmune hepatitis and myocarditis, accounting for about 1.26% of thymoma patients undergoing surgery in Beijing TongRen Hospital. Clinical data were retrospectively collected. All samples were harvested during surgical procedures, and analyzed to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Thymus is a crucial immune organ that has an impact on T-cell homeostasis and function. Thymic tumors such as thymoma have been associated with various autoimmune diseases, including myasthenia gravis (MG), Good's syndrome, dermatomyositis, Addison's disease, and rheumatoid arthritis [12]. These associations may be related to abnormalities in T-cell function.…”
Section: Resultsmentioning
confidence: 99%
“…Thymus is a crucial immune organ that has an impact on T-cell homeostasis and function. Thymic tumors such as thymoma have been associated with various autoimmune diseases, including myasthenia gravis (MG), Good's syndrome, dermatomyositis, Addison's disease, and rheumatoid arthritis [12]. These associations may be related to abnormalities in T-cell function.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the accumulation of intrahepatic CD8 + CD103 + perforin + T cells, the so-called tissue resident memory T cells, have been observed in pediatric patients with AIH, particularly in indeterminate acute liver failure ( 31 ). Moreover, a cohort study of 13 patients with hypertransaminasemia and thymoma demonstrated significantly decreased frequencies of CD8 T cells and an elevated CD4/CD8 ratio after thymectomy ( 32 ). As observed in the present case, liver histopathology showed predominant infiltration of CD8 T cells ( Fig.…”
Section: Discussionmentioning
confidence: 99%